The Relationship between Principal Supervision and Interpersonal Communication with the Work Ethic of Teachers - Desrina, Desrina; Fitria, Happy; Mulyadi, Mulyadi (Yayasan Sembilan Pemuda Indonesia, 2020)
This study aimed at analyzing the relationship between principal supervision and interpersonal communication partially and simultaneously with the work ethic of teachers at Prabumulih Public High School. This research was a survey research with a quantitative approach. The research subject was the teacher while the object of the research was the supervision of the principal and the interpersonal communication. The results obtained indicate that there is a relationship between the principal’s supervision and interpersonal communication partially and simultaneously significant with the work ethic of teachers in SMA Negeri Prabumulih.